(untitled) (Research, Society and Development, 2021)
Objective: to analyze the consumption of illegal and legal drugs and their consequences during pregnancy. Methodology: This is an integrative literature review article. the search was carried out in the databases of the VHL, Scielo, Lilacs, PubMED and Academic Google. The terms “Pregnancy complications”, “Illicit drugs” and “Pregnancy” were used as DeCs (Health Descriptors). original articles were included, indexed in the selected databases, in the languages: Portuguese and English; published between 2016 and 2021. Exclusion criteria were publications of theses, conference proceedings and the like, dissertations, monographs and articles that did not adhere to the theme. Results: It was found that among the most consumed legal drugs are alcohol and tobacco, among the illegal ones stand out marijuana, cocaine and crack. As for the consequences of use during pregnancy, it was identified that alcohol and tobacco are responsible for malformation, fetal alcohol syndrome, fetal hypoxia, low birth weight, premature birth, respiratory problems, neurological disorders, among others. In the mother, it causes gastric acidity, decreased respiratory protective reflexes, placental detachment, and premature birth. Crak and cocaine cause abortion, intrauterine growth retardation, and respiratory problems, hypertension, tachycardia and arrhythmia, heart attack and even death. Marijuana can lead to anancephaly. Final considerations: More studies addressing the topic, as well os workshops and lectures, are needed, with a focus on awareness of the consequences of drug use during pregnancy, which will bring positive results.